The Impact of Product Performance, Customer Service, and Human Resources on Repeat Purchase Behavior: The Mediating Role of Customer Satisfaction in the Insurance Industry - Fitriawaliyah Naibaho; Tri Inda Fadhila Rahma; Annio Indah Lestari Nasution (Jurnal Investasi Islam, 2026)
Repeat Purchases are one of the main goals for marketing, sales and Customer Service teams. This is because Repeat Purchases are a way to increase revenue and ensure customer retention. This research analyzes the influence of Product Performance, Customer Service, and Human Resources on Repeat Purchases through Customer Satisfaction at PT. Sun Life Financial Medan Branch. Sampling in this study used the Likert scale method with a total of 80 insurance participant respondents. This researcher used SEM (Structural Equation Modeling) data analysis, with the PLS (Partial least Square) approach, regression analysis test, validity test, reliability test, multiple linear regression analysis, hypothesis testing, determinant coefficient (R2) and path analysis techniques. The results of the research show that Product Performance has a significant influence on Repeat Purchases, Product Performance has a significant influence on Satisfaction, Customer Service has a significant influence on Customer Satisfaction, Human Resources has a significant influence on Repeat Purchases, Human Resources has a significant influence on Customer Satisfaction and Customer Satisfaction has a significant influence on Repeat Purchases at PT. Sun Life Financial Medan.